PENGARUH ENTREPRENURIAL MINDSET, DIGITAL LITERASI, DAN CERTIFICATION TERHADAP PERFORMANCE OF MSMEs: PERAN SELF EFFICACY SEBAGAI MODERATOR (Studi Pada UMKM di Kota Surakarta) - Septian Dwi Cahyo; Vincentia Indah Puspita Sari; Eka Kurnia Patmasari (ITB AAS Indonesia Surakarta, 2024)
The Surakarta City Government continues to strive to increase the number of MSMEs so that employment opportunities are greater than the workforce, this is done to reduce the poverty rate in Surakarta City. The purpose of this study was to determine the performance of MSMEs in Surakarta City which is influenced by entrepreneurial mindset, digital literacy, certification with the role of self-efficacy as a moderator. This study uses a quantitative approach and SEM WarpPLS Version 8.0 data processing tools. The number of samples in this study was 210 MSME actors in Surakarta City. The results showed that digital literacy and product certification had a positive effect on MSME performance, but entrepreneurial mindset did not have a positive effect on MSME performance. Meanwhile, for the role of moderation, the results showed that it was supported, thus strengthening the relationship between digital literacy and certification on MSME performance, but for entrepreneurial mindset the results were not supported.